2004
DOI: 10.1152/physiolgenomics.00031.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high glucose on gene expression in mesangial cells: upregulation of the thiol pathway is an adaptational response

Abstract: Pathological alterations in glomerular mesangial cells play a critical role in the development of diabetic nephropathy, the leading cause of end-stage renal disease. Molecular mechanisms mediating such alterations, however, remain to be fully understood. The present study first examined the effect of high glucose on the mRNA expression profile in rat mesangial cells using cDNA microarray. Based on variation-weighted criteria and with a false discovery rate of 4.3%, 459 of 17,664 cDNA elements examined were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 45 publications
1
41
1
Order By: Relevance
“…48 Relative Rab38 transcript abundance was estimated as the average of four measurements per cell line using the DD Ct method with glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a reference gene. 49 The average Rab38 expression in the control sh-GFP line was designated as 100%.…”
Section: Rab38 Expression In Pk1-rab38-sh Linesmentioning
confidence: 99%
“…48 Relative Rab38 transcript abundance was estimated as the average of four measurements per cell line using the DD Ct method with glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a reference gene. 49 The average Rab38 expression in the control sh-GFP line was designated as 100%.…”
Section: Rab38 Expression In Pk1-rab38-sh Linesmentioning
confidence: 99%
“…False discovery rate was determined by permutations as described previously. 48 The criteria of differential expression were then adjusted until an acceptable false discovery rate was obtained. The differentially expressed genes were annotated as described previously.…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…The differentially expressed genes were annotated as described previously. 16,17,48,49 Real-Time PCR Real-time quantitative PCR was carried out with the same RNA used in the microarray studies using the ABI Prism 7900HT sequence detection system and SYBR Green reagents from Applied Biosystems (Foster City, CA) as described previously. 48,49 The sequences of the primers used in this study are shown in Table 3.…”
Section: Gene Expression Profilingmentioning
confidence: 99%
“…The DNA microarray approach has been applied to the study of diabetes. Examples of tissues examined include ␤-cells (5,36), immune cells or organs (7,38), adipose tissue (25), the retina (11), skeletal muscle (23,30,40), and the kidney or kidney cells (24,31,37). Many of these studies have provided novel insights into the pathophysiology of diabetes and identified previously unsuspected mechanisms deserving further investigation.…”
mentioning
confidence: 99%